Peningkatan Hasil Belajar PKn Materi Peristiwa Sumpah Pemuda Melalui Metode Belajar PQ4R - Wahyu Triandono (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2021)
Subjects in elementary school require the activeness of Civics learning in Civics subject matter, students are expected to think critically and take advantage of the past to understand the present and the future. So we need a learning method that can present learning materials to students in the classroom, either individually or classically so that lessons can be learned, can be absorbed, can be reached, and utilized well by students. The PQ4R method is one that can be used to assist students in understanding learning materials to achieve learning objectives. This study aims to determine the improvement of Civics learning outcomes for the youth oath material through the PQ4R learning method. Collecting data used by researchers using observation, interviews, tests and documentation. This research is a classroom action research using the Kemmis & Mc Taggart model. The subjects of this study were third grade students of SDN Slawu 02 Jember. Results Based on the research, it shows that the use of the PQ4R learning method can improve Civics learning outcomes which are marked by student learning mastery which increases significantly between the results at the beginning or pre-cycle and in cycle 1 and cycle 2.